2018
DOI: 10.18632/oncotarget.25680
|View full text |Cite
|
Sign up to set email alerts
|

The role of E-cadherin and β-catenin in laryngeal cancer

Abstract: Epithelial cadherins with catenins form the E-cadherin-catenin complex that acts on cell-to-cell adhesion. The loss of these complex lead to the reduction or absence of epithelial cadherin expression in the cell membrane, cytoplasmic accumulation of β-catenin and its translocation to the nucleus, contributing to carcinogenic events. The objective of this study was to evaluate the expression of epithelial cadherin and β-catenin in patients with laryngeal tumor. A retrospective study of 52 patients with glottic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Cadherin‐1 (CDH1) or E‐cadherin is a single‐pass transmembrane protein that mediates homophilic cell‐cell interactions . Tumor progression is often associated with the functional loss of cadherin‐1 and the transition to a more motile and invasive phenotype . Further, cadherin‐1 also plays several roles in apoptosis progression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadherin‐1 (CDH1) or E‐cadherin is a single‐pass transmembrane protein that mediates homophilic cell‐cell interactions . Tumor progression is often associated with the functional loss of cadherin‐1 and the transition to a more motile and invasive phenotype . Further, cadherin‐1 also plays several roles in apoptosis progression .…”
Section: Discussionmentioning
confidence: 99%
“…28 Tumor progression is often associated with the functional loss of cadherin-1 and the transition to a more motile and invasive phenotype. 28,29 Further, cadherin-1 also plays several roles in apoptosis progression. 30 In this study, S. cumini treatments caused significant upregulation of CDH1 protein and gene expressions.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was reported by Nardi et al who evaluated by IHC analysis the expression of E-cadherin and β-catenin in 52 LSCC tissue samples. The authors showed that E-cadherin and β-catenin decrease lead to a greater local aggression and cervical metastases occurrence [ 53 ]. In a recent retrospective study, EMT-associated markers’ expression (E-cadherin, N-cadherin, β-catenin, and ZEB2) was analyzed in 76 stage I–IVa LSCC patients treated with surgery, with and without LNM, using IHC analysis.…”
Section: Molecular Markers For Clinical Management Of Lsccmentioning
confidence: 99%
“…Interestingly, low protein expression of E-cadherin in oral SCCs correlates with recurrence, poor cellular differentiation, metastatization and shorter overall survival [152,153]. Moreover, E-cadherin expression is positively correlated with the stages of oral SCC progression, as its expression increases during the transition from dysplasia to oral cancer [154,155].…”
Section: Mdm2 and E6ap Restrain P53 In Sccsmentioning
confidence: 99%